The Coal Bio-Solubilization Technology for Energy Security - Zahara P., Lis Ocktty; Permatasari, Cantika Setya; Supriyadi, Imam; Andreyani, Anggun (Purnomo Yusgiantoro Center, 2021)
The petroleum needs as primary energy in Indonesia more increasing, while the petroleum reserves were more depleting so that coal utilization as primary energy is inevitable. Therefore, needed a solution in coal utilization which is environmentally friendly (clean energy) to fulfill the national energy needs. This research is based on the analysis and study of 11 research journals related to coal bio-solubilization technology published in the period 1994 to 2019. The results show that low-rank coal has the potential as the environmentally friendly alternative energy by converting solid coal into liquid phase equivalent to gasoline and diesel which is sulfur and nitrogen-free with bio-solubilization technology. However, this bio-solubilization technology has the disadvantage of the slow coal degradation process into the liquid phase because it only relies on the microorganism’s ability. The application of coal bio-solubilization technology as the alternative energy to support energy security requires genetic engineering and catalyst technology research support to improve the microorganism’s ability to increase the coal degradation rate.